Potential of Rumex crispus Root Infusion Against the Growth of Staphylococcus epidermidis - Reva Nurpadila (12th International Scholars Conference 2025, 2026)
Acne vulgaris (AV) is a chronic inflammatory disorder of pilosebaceous units that is commonly seen in young adults. The main factors involving AV are increased sebum production and bacterial inflammation. One of the bacteria commonly associated AV is Staphylococcus epidermidis (SE). Antibiotics for treating AV may lead to side effects such as skin irritation or rashes, and in certain cases, can trigger severe allergic reactions. Medicinal plants are considered safer than antibiotics. Biological activities and effectiveness of medicinal plants have been evaluated both in traditional medicine and across various scientific disciplines. The studies conducted so far show that medicinal plants represent a significant source of antioxidants and compounds with antibacterial effect. Rumex crispus (RC) has a long history of use in herbal medicine and is traditionally regarded as beneficial for individuals with persistent skin conditions across various medical traditions. This study purpose is to find out the anti-bacterial potential of RC infusion to treat acne problem at concentrations of 5%, 10%, and 15% against SE with four replications. The result of the study shows that the zone of inhibition diameters was categorized moderate and there was no significant difference between each concentration (p value = 0.375). The result of the study concluded that RC infusion might slow SE growth enough to help, but may not be sufficient as a sole treatment for AV at the tested concentrations.